Menakar Motivasi Belajar Siswa Di Masa Pandemi - Krismiyati, Krismiyati (Universitas Sebelas Maret, 2022)
This research aims to find out how the learning motivation of class II students at SDN 2 Gombang is during the pandemic. This type of research uses a qualitative descriptive method with data collection techniques through interviews with class II teachers at SDN 2 Gombang. The results of the research show that students' learning motivation during online learning during the pandemic is low and has decreased compared to learning before the pandemic. One of the things that influences this is the lack of direct interaction between teachers and students.